Analisis Customer Insight dan Perilaku Konsumen sebagai Fondasi Strategi Pemasaran yang Efektif - Haryati Pertiwi; Ahmad Fikri Sidharta; Arfiani Yulianti Fiyul (Journal Of Business, Finance, and Economics (JBFE), 2026)
This article examines the role of customer insight and consumer behavior analysis as the foundation for developing effective and sustainable marketing strategies. In the context of increasingly fierce business competition, companies must understand not only who their customers are, but also how they think, feel, and make decisions. This study employs a descriptive-qualitative approach through literature review and case study analysis of five leading companies in Indonesia: Shopee, Tokopedia, Gojek, Unilever (Sunsilk), and Starbucks. The findings reveal that consumer behavior is shaped by four interacting factors psychological, social, cultural, and economic across all stages of the purchase decision process. Customer insight generated through systematic data collection and interpretation drives product innovation, enhances marketing campaign effectiveness, and strengthens long-term customer loyalty. This research affirms the critical importance of investing in consumer analytics capabilities as a source of competitive advantage in the digital era.